Financial equilibrium as basis for enterprise’s sustainable development: economic and mathematical foundation - Gudz, Tetiana (Technology audit and production reserves, 2017)
Using correlation-regression analysis the impact of financial equilibrium on the sustainable development of the enterprise is investigated. The current insufficient level of methodology for assessing enterprise’s sustainable development causes scientific search for its diagnosis’s special tools. Relationship between enterprise’s sustainable development and its financial situation is poorly researched. The economic-mathematical model of financial equilibrium’s impact on enterprise’s sustainable development is developed. It is described by influence of four factors on financial potential’s internal growth ratio, which is an indicator of enterprise’s sustainable development. Influencing factors are first and second indicators of financial equilibrium, financial leverages in assets and capital. The economic-mathematical model of the relationship between the coefficient of internal growth of the financial potential of the enterprise and the indicators of its financial equilibrium is developed. The obtained economic-mathematical model allows to predict the tendency of sustainable development depending on the actual establishment of enterprise’s financial equilibrium as well as to model the probable changes in its financial status. Application of the economic-mathematical model is aimed at improving quality level of enterprise’s financial management.